TANGGUNG GUGAT PT HASSANA BOGA SEJAHTERA ATAS PEREDARAN MAKANAN BAYI (PENDAMPING ASI) DENGAN MEREK BEBILUCK YANG MENGANDUNG BAKTERI E.COLI DAN BAKTERI COLIFORM - NASRAH NASRAH; Lanny Kusumawati; Heru Susanto (Perpustakaan Universitas Surabaya, 2018)
Producer is any individual or legal entity providing goods and / or services for human needs (consumer). The needs of consumers produced and traded by the producers is one of them is food products such as food that is needed by the baby that is the companion breast milk companion food. breast milk companion food is a food intake given to infants aged 6-24 months apart from breast milk. In the current development of producers in producing food products often do not pay attention to the rights and obligations of consumers and producers themselves that have been regulated in the Consumer Protection Act, such as in producing and trading its products manufacturers do haven't license marketing from the authorities and in producing the food product of the business actor does not pay attention to the food safety problem so that the food product contains a bacteria that is Coliform bacteria and E.coli bacteria.